Social security reform in advanced countries : evaluating pension finance - Ihori, Toshihiro, 1952-; Tachibanaki, Toshiaki, 1943- (Routledge contemporary economic policy issues, 2003)
This book brings together internationally-renowned scholars to evaluate the effect of recent social security reforms in advanced countries (pension programmes in particular) and to suggest policy reforms for the future.